Natural Variation of Cold Deacclimation Correlates with Variation of Cold-Acclimation of the Plastid Antioxidant System in Arabidopsis thaliana Accessions - Juszczak, Ilona; Cvetkovic, Jelena; Zuther, Ellen; Hincha, Dirk K.; Baier, Margarete (Frontiers in Plant Science, 2016)
Temperature variations impact on the balance between photosynthetic electron transport and electron-consuming assimilation reactions and transiently increase generation of reactive oxygen species (ROS). Previous studies demonstrated that the expression of C-repeat binding factors (CBFs), which activate cold acclimation reactions, respond to chloroplast ROS signals and that cold deacclimation is partly halted for days after the transfer of acclimated plants to optimal growth conditions in four Arabidopsis accessions from cold-continental habitats. We hypothesized that these accessions differ from others in the regulation of the plastid antioxidant system (PAS). In the present study, we compared the expression intensity of the 12 most prominent PAS genes for peroxidases, superoxide dismutase and low molecular weight antioxidant regenerating enzymes in 10 Arabidopsis accessions with regulation of CBF and COR (cold regulated genes) transcript levels and cold-regulated metabolite levels prior to cold, after 2 week long cold acclimation and during the first 3 days of deacclimation. In the accessions with prolonged activation of cold responses, by trend, weaker induction of various cold-inducible PAS genes and stronger decreases in the expression of negatively cold-regulated PAS genes were observed. Low PAS gene expression delayed the post-cold decrease in H2O2 levels after transfer of the plants from cold to optimal growth conditions. We conclude that weaker expression of various PAS genes in the cold is an adapted strategy of the Arabidopsis accessions N14, N13, Ms-0, and Kas-1 to avoid full inactivation of cold-responses in the first days after the end of the cold period.